2014
DOI: 10.1177/0004867414528589
|View full text |Cite
|
Sign up to set email alerts
|

Depression and chronic kidney disease: A review for clinicians

Abstract: Depression is common in CKD and is associated with a significant risk of adverse outcomes. Given the importance of this issue, there is now an urgent need for well-conducted randomised trials of interventions for depression in CKD in order to provide information on the safety and efficacy of treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 91 publications
2
78
0
2
Order By: Relevance
“…Although the association between depression and clinical outcomes in patients with CKD were well documented [18,33], studies focusing on the role of depression as a factor for primary prevention of CKD were rare, especially in hypertensive group. In our study, we found that moderate or greater depression increased the risk for developing decreased GFR in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association between depression and clinical outcomes in patients with CKD were well documented [18,33], studies focusing on the role of depression as a factor for primary prevention of CKD were rare, especially in hypertensive group. In our study, we found that moderate or greater depression increased the risk for developing decreased GFR in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is evidenced that depression was prevalent and QoL was lower among CKD patients [12,13,14,15,16]. Several studies linked depression or low QoL to increased mortality risk in CKD patients [17,18,19], indicating the importance and potential effects of depression and QoL during CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is one of the most prevalent mental health conditions in patients with chronic kidney disease (CKD) [1][2][3][4] ; furthermore, it is an important determinant of impaired quality of life. 5,6 Among kidney transplant (kTx) recipients, depression is associated with reduced adherence and also with increased morbidity, graft loss, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is associated with reduced treatment adherence and quality of life as well as elevated rates of hospitalization and mortality. The interaction of CKD and depression is reciprocal with one condition worsening the other [51]. Anxiety symptoms are also common among CKD patients but when they accompany symptoms of depression do not add to the risk of poor clinical outcomes beyond that associated with depression alone [52].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%